Diagnostic Approaches and Management of Subacute Sclerosing Panencephalitis in Children - Nurul Hidayah; Andreas Budi Wijaya (Fakultas Kedokteran Universitas Lambung Mangkurat, 2020)
Abstract: Subacute Sclerosing Panencephalitis (SSPE) is a progressive neurodegenerative disease that attacks the central nervous system, especially in the population of children and early adolescents, due to persistent measles virus infection. The incidence of SSPE is quite rare, and data shows that in developing countries it is still quite high compared to developed countries. Diagnosis is based on clinical, supporting examinations such as EEG, as well as increased antibodies against measles virus in serum and cerebrospinal fluid. Symptoms can include changes in behavior, myoclonus, memory problems, and persistent pyramidal or extrapyramidal movements. Management to date has not provided satisfactory results and is individualized. Most SSPE patients experience a progressive and gradual course, leading to death within 1-3 years. The challenge of SSPE in children is the approach to diagnosis and management. Until now, the approach to treating SSPE in children is still based on the pathophysiological mechanisms from several existing research studies. That why therapy guidelines for children with SSPE are still varied. This paper aims to discuss the topic of SSPE in children with a major focus on diagnostic and therapeutic approaches based on the latest scientific evidence. Keywords: Subacute Sclerosing Panencephalitis (SSPE), children, diagnosis, therapy